P0440EPIDEMIOLOGICAL AND CLINICAL CHARACTERSTICS OF IGA NEPHROPATHY PATIENTS IN TURKEY: TSN-GOLD WORKING GROUP. (6th June 2020) - Eren, Necmi; Gursu, Meltem; Cebeci, Egemen; Turkmen, Aydin; Yeter, Hasan Haci; Seyahi, Nurhan; Piskinpasa, Serhan Vahit; Ersoy, Alpaslan; Basturk, Taner; Manga Sahin, Gulizar; Kocak Yucel, Fatma Sibel; Genç, Ahmed Bilal; et al.
Abstract: Background and Aims: According to the data of the Turkish Society of Nephrology-Glomerular Diseases Working Group (TSN-GOLD Working Group), IgA nephropathy is the most common primary glomerular disease in Turkey. The purpose of this study was to investigate the epidemiological and clinical data of IgA nephropathy patients in Turkey. Method: 4399 patients with primary glomerular diseases from 47 centers who were followed up between May 2009 and May 2019 were included in the study conducted by TSN-GOLD Working Group. 524 patients were excluded due to lack of pathological data. Among the remaining patients, demographic, clinical and laboratory data of 994 patients with IgA nephropathy were analyzed. Results: The median age of the patients was 37 (28-47) years, and 37.3% of them were female. The laboratory and clinical data at the time of diagnosis is presented in Figure-1, and biopsy indications are described in Figure-2. The median number of glomeruli was 16 (IQR: 3.5-4.3), sclerotic glomeruli was 2 (IQR: 1-5), and segmental sclerotic glomeruli was 1 (IQR: 1-2). Exudative changes, subendothelial and subepithelial deposition were present in 566 patients (56.9%), 46 patients (4.6%) and in 38 patients (3.8%), respectively. 662 (66.1%) and 611 of the patients (61.4%) had tubular atrophy and interstitial fibrosis in varying degrees, respectively. 672 (%67.6) and 416 patients (%41.9) had interstitial inflammation and vascular changes, respectively. In immunofluorescence staining, 18%, 30.1%, 4.4%, 68% of the patients had IgG, IgM, C1q and C3 positivity, respectively. Crescentic glomeruli were detected in 227 patients (3.3 ± 3.1 glomeruli). Patients with crescentic glomeruli had significantly higher proteinuria and lower eGFR than the patients without [2203 mg/day (15-26078) vs 1807 mg/day (15-29112); p=0.001; 55.3 ml/min/1.73 m 2 (3.72-141.9) vs 72 ml/min/1.73 m 2 (3.84-150.81); p<0.001, respectively]. Oxford classification was applied to 544 patients. Endocapillary hypercellularity (E1), mesengial hypercellularity (M1), tubular atrophy and interstitial fibrosis (T1 and T2), segmental sclerosis (S1) were present in 126 (13%), 425 (42.8%), 306 (30.8%) and 325 patients (%32.7), respectively. Proteinuria levels were higher in patients with endocapillary hypertrophy, mesengial hypercellularity, tubular atrophy-interstitial fibrosis and segmental sclerosis. eGFR levels were lower in patients with endocapillary hypertrophy, tubular atrophy-interstitial fibrosis and segmental sclerosis (Figure-3). Conclusion: In this study we found that, the most common presentation of IgA nephropathy patients in our country was asymptomatic urinary abnormalities followed by nephritic and nephrotic syndrome. Higher proteinuria and lower eGFR values in patients with crescentic glomeruli, support the adoption of crescentic lesions in the new Oxford classification (MEST-C) to predict more precise outcome of IgA nephropathy patients. The high number of patients to whom the Oxford classification was applied provided us with the opportunity to examine the clinical reflections of pathological features. Evaluation of the follow-up data of the patients will give us the possibility to reveal the effect of initial clinical and pathological features on clinical findings and renal outcome.